Comparison of the Effectiveness of Two Levels of Suction Pressure on Oxygen Saturation in ARDS Patients - Dadang Heryandi; Sahrudi Sahrudi; Artetha Mutiara Pujiantana; Norma Norma; Farida Murtiani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Patients in the Intensive Care Unit (ICU) often require mechanical ventilators, necessitating close monitoring and care, including regular evaluations of oxygen saturation levels. Suction procedures are conducted in the ICU to maintain airway patency, reduce sputum retention, and prevent pulmonary infections. The effectiveness of suction procedures can vary based on the suction pressure applied, which may impact patient outcomes differently. The purpose of this study was to determine the effectiveness of suction action with pressures of 130 mmHg and 140 mmHg on increasing oxygen saturation in ARDS patients with mechanical ventilation in the ICU. The research employed a quantitative approach using a quasi-experimental pre-post design with a control group. A sample of 30 ICU patients was divided into two groups: one group of 15 patients received suctioning at a pressure of 130 mmHg, while the other group of 15 received suctioning at 140 mmHg. Oxygen saturation levels were measured using pulse oximetry before and after the suction intervention. The procedures were conducted in accordance with the hospital's Standard Operating Procedure (SOP). Data were analyzed univariate and bivariate using the T-test. There was a significant increase in oxygen saturation after suctioning with both pressures. For the 130 mmHg group, the average increase in oxygen saturation was 5.933 with a P-value of 0.000. For the 140 mmHg group, the average increase was 6.400 with a P-value of 0.000. However, there was no statistically significant difference between the two suction pressures in terms of the overall increase in oxygen saturation, with a P-value of 0.567. Both 130 mmHg and 140 mmHg suction pressures were effective in improving oxygen saturation in ARDS patients on mechanical ventilation in the ICU. Hospitals should ensure structured and consistent monitoring of suction procedures in accordance with hospital SOPs to optimize patient outcomes.